2005
DOI: 10.1007/bf03030408
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural changes of cell organelles inArabidopsis stems after gamma irradation

Abstract: We examined ultrastructural changes of the cell organelles of Arabidopsis stems in response to gamma irradiation.Seedlings treated with 0 to 5 Gy developed normally, while height growth in plants exposed to 50 Gy was significantly inhibited. Based on TEM observations, the chloroplasts were extremely sensitive to such irradiation, in particular, the thylakoids were heavily swollen, some portions of the mitochondria and endoplasmic reticulum were structurally altered, and the plasmalemma had pulled away from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
85
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(91 citation statements)
references
References 13 publications
4
85
0
2
Order By: Relevance
“…Previous studies have also reported divergent results depending on the sensitivity of the plant species and the radiation dose applied. Wi et al [8] reported no alterations in the height of A. thaliana seedlings 12 days after gamma irradiation up to 5 Gy, while exposure to 50 Gy significantly decreased plant height. Irradiation effects on two generations of P. sativum seedlings were studied by Zaka et al [3] reporting doses above 6 Gy significantly inhibited plant growth and productivity in the first generation while the effects were even more severe in the second generation.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous studies have also reported divergent results depending on the sensitivity of the plant species and the radiation dose applied. Wi et al [8] reported no alterations in the height of A. thaliana seedlings 12 days after gamma irradiation up to 5 Gy, while exposure to 50 Gy significantly decreased plant height. Irradiation effects on two generations of P. sativum seedlings were studied by Zaka et al [3] reporting doses above 6 Gy significantly inhibited plant growth and productivity in the first generation while the effects were even more severe in the second generation.…”
Section: Resultsmentioning
confidence: 98%
“…Pine trees are known to be very radiosensitive and while irradiation with 0.1-1 Gy already caused low injuries, irradiation with more than 60 Gy resulted in a massive mortality and no regeneration of pine trees after the Chernobyl accident [7]. For A. thaliana seedlings on the other hand, Wi et al [8] demonstrated that seedlings developed normally after exposure to 5 Gy, while plant height was significantly reduced following exposure to 50 Gy. In general, a screening value, representing a dose rate affecting 5% of the plant species at a 10% level, presented as a predicted no effect dose rate, of 70 Gy h −1 was derived for plants [9].…”
Section: Introductionmentioning
confidence: 99%
“…The effects of gamma radiation on some properties of many plants and seeds were investigated by researchers (Mahmoud, 2002;Wi et al, 2005;Rahimi and Bahrani, 2011). In our study, the crude oil yield of S. chinensis Arizona-A42 seeds was affected by gamma rays in a significantly positive way.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have investigated the effects of gamma radiation on plants, including changes at the morphological, physiological and biochemical levels. These effects include changes in the plant photosynthetic pigments, composition of chemical, cellular structure and crude oil yield (Wi et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Gamma rays belong to ionizing radiation and interact on atoms or molecules to produce free radicals in cells. These radicals can damage or modify important components of plant cells and have been reported to affect differentially the morphology, anatomy, biochemistry and physiology of plants depending on the irradiation level (Kim et al 2004;Wi et al 2005;El Sherif et al 2011). This study builds a foundation for optimization of medium components and conditions as a first step towards further research for commercialization.…”
Section: Discussionmentioning
confidence: 99%